Ahmed Deedat’s Methodology in Comparative Theological Discourse and Zakir Naik’s Integration - Islam, Mohammad Aminul; Ushama, Thameem (Advances in Social Sciences Research Journal, 2024)
Ahmed Deedat has a distinctive approach and unique way of formulating his da’wah materials and their organisation. Similarly, he presented his evidence and arguments to prove his point in the debates he engaged in, the talks he delivered, and the books he authored. Hence, this paper aims to exhibit Deedat’s methodology in studying religions, focusing on his preparation for a debate, delivering it followed by a question-answer session and the extent to which Zakir Naik incorporated it. Besides that, Deedat’s short biography and contributions to the comparative theological study are explored. An analytical and comparative method is employed in this study. The most significant finding of this research is Naik’s realisation in his fifties as a dāᶜin in all situations must be versatile in his preaching and propagation.